Motivations and Consequences of Alcohol Use Among Heavy Drinking Nonstudent Emerging Adults. (November 2017) - Lau-Barraco, Cathy; Linden-Carmichael, Ashley N.; Hequembourg, Amy; Pribesh, Shana
Research suggests that nonstudent emerging adults may be at elevated risk of alcohol-related problems in adulthood. The present study utilized a qualitative approach to broaden our understanding of the drinking-related perceptions and experiences of heavy drinking nonstudents, with the ultimate goal of generating meaningful knowledge that could aid intervention planning. Research aims were to identify nonstudent (a) drinking motivations and (b) drinking consequences. Eleven focus groups were conducted ( n = 64 participants). Data analytic techniques were used to code transcripts and generate themes emerging from the group data. Three main themes emerged regarding nonstudent reasons for drinking (i.e., emotional, social, enhanced experiences). Four prominent themes were identified for drinking consequences (i.e., physical health, psychological health, risk-taking, life functioning). Our findings underscore several considerations related to intervening with this at-risk and understudied population.